Avaliação de forças liberadas por alças em forma de gota utilizadas em mecânica ortodôntica para fechamento de espaços - D'Ornellas, Mauro Cordeiro (2010)
The purpose of this research was to investigate the influence of height, crosssection and metal alloy in the mechanical act of teardrop loops used in incisors retraction and in en masse retraction of incisors and canines, aiming analyze the mechanical behavior of these loops in relation to optimum forces presented in the literature. Two hundred and forty loops were submitted to a tensile load on the testing machine considered heights of 6mm, 8mm and 10mm; cross-sections of 0.018in.x 0.025in and 0.019in.x 0.025in and wire materials of stainless steel and beta-titanium alloys. It was obtained magnitudes of horizontal force (N) and load-deflection (N/mm) for each loop across activations of 0.5mm, 1mm, 1.5mm, 2mm and 2.5mm. The results showed that height (p<0.01), cross-section and metal alloy (p<0.05) were considered significant factors with reference to horizontal force and load-deflection. There was no influence of one factor but a combination of these trying to achieve very light forces. This study suggest that is necessary a large orthodontic biomechanics knowledge with respect to loops design used in incisors retraction and in en masse retraction of incisors and canines, selecting adequate height, crosssection and metal alloy.